AQUACULTURE PRODUCTION OPTIMIZATION MODEL OF BREBES REGENCY - Safitri, Diah; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the combination of aquaculture production in Brebes District and to know the intervals that might occur in variables so that the optimization model can still be used. The research variable consists of decision variables, namely the amount of aquaculture commodities that must be produced to achieve maximum profit. The commodities in question are shrimp, tilapia, catfish, milkfish, and seaweed. The constraint variable is the production factor used in aquaculture activities, including land, seeds, feed and fertilizer, and operational costs. The method of data analysis in this study uses Linear Programming analysis and sensitivity analysis. The type of data used is primary data from interviews with aquaculture households in Brebes District. The results showed the maximum profit from aquaculture production in Brebes District can be obtained when the number of vaname shrimp produced was 975,383.5 kg, catfish as much as 1,985,898 kg, milkfish as much as 885,986.6 kg, and seaweed as much as 2,532,448 kg. From the combination of aquaculture production, it can be seen that the maximum amount of profit obtained is Rp. 111,590,500,000 for one cultivation cycle. Suggestions: 1) strengthen the institutional household of aquaculture. 2) The government is expected to provide direction and incentives to cultivation FHs related to achieving production combination targets that produce maximum profits. 3) In the future, it is hoped that the related offices can have a more complete database on the fisheries sector, so that the analysis carried out has accurate results. Tujuan penelitian ini adalah mengetahui kombinasi produksi perikanan budidaya di Kecamatan Brebes serta mengetahui intervalperubahan yang mungkin terjadi pada variabel sehingga model optimasi masih dapat digubakan. Variabel penelitian terdiri dari variabel keputusan yaitu jumlah komoditas perikanan budidaya yang harus diproduksi untuk mencapai keuntungan maksimal. Adapun komoditas yang dimaksud adalah udang, nila, lele, bandeng, dan rumput laut. Variabel kendala adalah faktor produksi yang digunakan dalam kegiatan budidaya, diantaranya adalah lahan, bibit, pakan danpupuk, dan biaya operasional. Metode analisis data dalam penelitian ini menggunakan analisis program linear dan analisis sensitivitas. Jenis data yang digunakan adalah data primer dari hasil wawancara dengan rumah tangga perikanan budidaya di Kecamatan Brebes. Hasil penelitian menunjukkan euntungan maksimal dari produksi perikanan budidaya di Kecamatan Brebes dapat diperoleh ketika jumlah udang vaname yang diproduksi sebanyak 975.383,5 kg, lele sebanyak 1.985.898 kg, bandeng sebanyak 885.986,6 kg, dan rumput laut sebanyak 2.532.448 kg. Dari kombinasi produksi perikanan budidaya tersebut, dapat diketahui jumlah keuntungan maksimum yang diperoleh sebesar Rp. 111.590.500.000 untuk satu siklus budidaya. Saran: 1) memperkuat kelembagaan rumah tangga perikanan budidaya. 2) Pemerintah diharapkan memberikan arahan dan insentif kepada RTP budidaya terkait pencapaian target kombinasi produksi yang menghasilkan keuntungan maksimum. 3)Kedepannya diharapkan dinas terkait dapat memiliki database mengenai sektor perikanan yang lebih lengkap, sehingga analisis yang dilakukan memiliki hasil yang akurat.